Unlocking PHP’s Potential: An All-Inclusive Approach to Server-Side Scripting - Deming, Chunhua; Baddam, Parikshith Reddy; Vadiyala, Vishal Reddy (Engineering International, 2018)
PHP powers many dynamic and interactive websites in the ever-growing world of web development. PHP was initially called "Personal Home Page," but it has since become the Hypertext Preprocessor we know. This detailed article examines PHP (Hypertext Preprocessor), a dynamic server-side scripting language that has shaped the digital landscape since 1994. PHP has grown from a tool for managing a personal website to a flexible language powering much of the web. A detailed look into PHP object-oriented programming reveals its organizational benefits, while a separate section covers session management, form handling, and database interfaces in web development. PHP application security comes first, addressing common vulnerabilities and recommending best practices. The study covers PHP frameworks, development tools, scalability, and performance optimization. Finally, it considers PHP’s role in Web 3.0 and its future in upcoming technologies. This PHP exploration seeks to help developers master and innovate in the ever-changing web development landscape.